Bilingual education in monolingual contexts: a comparative perspective. Issue 1 (2nd January 2020) - Rumlich, Dominik
ABSTRACT: The main aim of this article is to evaluate the outcomes presented in the previous articles in relation to similar projects and studies conducted in monolingual contexts in other parts of Europe as well as Latin America, where bilingual education and CLIL are increasingly being embraced in the official curricula. The effects of CLIL on L1, L2 and content learning (from a quantitative standpoint) and the way in which bilingual education and CLIL programmes are playing out at all organisational and curricular levels (from a qualitative point of view) in these different contexts will be discussed in relation to the outcomes obtained in the longitudinal macro-study presented in the previous contributions of this special issue. The overarching conclusions, which this comparative perspective allows for, will be highlighted, discerning possible patterns that emerge, pinpointing potentially discrepant findings and underscoring the main lessons learned from CLIL implementations across diverse monolingual settings.